Development of science about crop rotations in systems of agriculture of Ukraine in context of activity of scientific school of Institute of agriculture of steppe zone of NAAS - Kovalenko, Nataliya (Skhid, 2014)
On the basis of the archived materials and labours of scientists pre-conditions of becoming and development of scientific school are certain from development of effective crop rotations in the systems of agriculture to central and north Steppe of Ukraine in Institute of agriculture of steppe zone of NAAS. It is set that on the modern stage basic activity of scientific school is sent to development: basic elements of the ecologically balanced crop rotations in the systems agricultures of steppe zone, that provides the receipt of high-quality products, extended recreation of fertility of soil and guard of environment; scientific government of the agrarian systems and introduction of crop rotations productive potential bases in the systems of agriculture of steppe zone, adapted to the natural environment; basic elements of the ecologically balanced crop rotations in the systems of agriculture of steppe zone on the basis of data of agrarian and ecological diagnostics that will provide the stable receipt of high-quality products and extended recreation of fertility of black earth; crop rotations in the systems of agriculture during optimization of correlation of the landed lands, application of effective technologies of production of agricultural goods in the zone of Steppe. Basic directions of activity of scientists-founders of scientific school, and also their students and followers and their contribution, are set to development of science about crop rotations in the systems of agriculture in Ukraine and world. Their ponderable long-term experience and thorough knowledge from the problems of development of crop rotations matter very much and actuality for the future scientists of our state.